Analysis of the Influence of Bank-Specific Factors on Revenue-Sharing Financing at Islamic Commercial Banks in Indonesia 2019 – 2023 - Latifah Nur Arifah; Ruhadi Ruhadi; Teguh Dwi Arsyah; Farhan Ramdhani Istianandar (Journal of Applied Islamic Economics and Finance, 2026)
This study aims to analyze the effect of bank-specific factors on profit-sharing-based financing at Islamic Commercial Banks in Indonesia for the 2019-2023 period. The independent variables used in this study include Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR) and Third Party Funds (DPK). While the dependent variable is profit sharing financing (Mudharabah and Musyarakah). This study uses a quantitative approach with a panel data regression analysis method that combines time series and cross section data from officially published financial reports of seven Islamic Commercial Banks. This research is expected to show a significant relationship between bank-specific factors on Mudharabah and Musyarakah financing. So that it can contribute in increasing the portion of Mudharabah and Musyarakah financing as the core business of Islamic banking.